Оптимізація складу комплексного антиоксиданту - Семченко, Галина Дмитрівна; Бражник, Діна Анатоліївна; Повшук, В. В.; Рожко, І. М.; Старолат, Олена Євгенівна (НТУ "ХПІ", 2015)
В роботі представлено результати оптимізації комплексного антиоксиданту, який складається з Al, етилсилікату та оксалату нікелю, для захисту від окиснення графіту в периклазовуглецевих виробах. Встановлено залежність розподілу показників міцності зразків і відкритої поруватості від вмісту компонентів в складі комплексного антиоксиданту. Показано, що незалежно від співвідношення компонентів в складі комплексного антиоксиданту відкрита поруватість периклазовуглецевих вогнетривів після термообробки при 180-200 °С не перевищувала 17 %.

The protection of carbon from oxidation at high temperatures is carried out by using antioxidants. Development of new complex of antioxidants and their distribution around the particles of graphite in the carbon sheaf of periclescarbon refractories is presented a considerable practical interest. The results of the optimization of complex antioxidant consisting of Al, ethylsilicate and nickel oxalate, for protect against oxidation of carbon in periclescarbon products are presented. The dependence of the samples strength rates distribution and open porosity from the content of components in the composition of complex antioxidant are found. It is shown that irrespective of the components ratio in the composition of the complex antioxidant the open porosity periclascarbon se refractory after heat treatment at 180–200 °C does not exceed 17 %. High porosity may be related to the fact that during the temperature heat treatment the gaseous products of decomposition of nickel salt are allocated as a result of physicalchemical transformations of nickel oxalate. Therefore, synthesized precipitate of nickel oxalate has heat advisable before using of nickel organic precursor for remove of decomposition products of salt.
Optimization of complex antioxidant composition
Keywords: етилсилікат; периклаз; оксалат нікелю; ethylsilicate; periclas; nickel oxalate